FAKTOR-FAKTOR YANG MEMPENGARUHI KUALITAS AUDIT - Shagti, Ruhita; Puspita, Erna; Sugeng (Universitas Nusantara PGRI Kediri, 2022)
This study was motivated by the finding that industrial audit quality is poor. Trustworthy financial reports are crucial for making decisions, so audit quality is highly valued. This research examines the impact of audit tenure, audit fees, firm size, and KAP size on IDX audits in 2019–2021. Quantitative methods including post hoc analysis were used in this study. 50 manufacturing firms were analyzed using logistic regression in SPSS for Windows 21. In this study, (1) audit tenure impacts audit quality. (2) The audit fee is a major factor in audit quality. (3) Firm size affects audit quality. (4) KAP size impacts audit quality. There's a strong correlation between audit quality and audit experience, audit fee, company size, and KAP size.